Architectures of the invisible hand: envisioning capital in Joseph Conrad's Singapore. Issue 1 (2nd January 2020) - Vandertop, Caitlin
ABSTRACT: In recent years, critical attention has shifted away from the subject of Conrad's imperial politics and towards his representation of late nineteenth-century global capitalism, which extends panoramically from the business houses of London, Brussels and San Francisco to commodity frontiers as diverse as Malay tobacco plantations, African ivory lands and Latin American silver mines. This paper explores Conrad's engagement with capitalism and its representability within his portrait of late nineteenth-century Singapore in the wake of a financial crisis. Drawing on Susan Buck-Morss's 'Envisioning Capital', as well as Fredric Jameson's essay on architecture and finance, 'The Brick and the Balloon', the paper reads Conrad's proto-postmodern urban landscape and porous, ethereal architecture as evidence of the visual and representational difficulties generated within a major colonial 'laboratory' of liberal economics. Yet, by shifting in focus from the city to its outlying plantations, Conrad is seen to confront abstract capital with territory, ether with matter, and free-market narratives of the 'invisible hand' with the absent cause of racialized and indentured plantation labour.